Acrylamide inhibits vaccinia virus through vimentin‐independent anti‐viral granule formation. (3rd May 2021) - Wood, Jennifer J.; White, Ian J.; Samolej, Jerzy; Mercer, Jason
Abstract: The replication and assembly of vaccinia virus (VACV), the prototypic poxvirus, occurs exclusively in the cytoplasm of host cells. While the role of cellular cytoskeletal components in these processes remains poorly understood, vimentin—a type III intermediate filament—has been shown to associate with viral replication sites and to be incorporated into mature VACV virions. Here, we employed chemical and genetic approaches to further investigate the role of vimentin during the VACV lifecycle. The collapse of vimentin filaments, using acrylamide, was found to inhibit VACV infection at the level of genome replication, intermediate‐ and late‐gene expression. However, we found that CRISPR‐mediated knockout of vimentin did not impact VACV replication. Combining these tools, we demonstrate that acrylamide treatment results in the formation of anti‐viral granules (AVGs) known to mediate translational inhibition of many viruses. We conclude that vimentin is dispensable for poxvirus replication and assembly and that acrylamide, as a potent inducer of AVGs during VACV infection, serves to bolster cell's anti‐viral response to poxvirus infection.